Epidemiology and outcomes of severe acute malnutrition (SAM) patients in Nutrition Stabilization Center (NSC) Gilgit, a retrospective study - Ghafoor, Muneeba; Hussain, Azhar; Yaqub, Sughra; Hussain, Wajahat; Batool, Sabahat (International Journal of Pathology, 2026)
Background: Severe Acute Malnutrition (SAM) is a critical health issue in Pakistan, particularly in remote regions like Gilgit-Baltistan, due to remoteness, lack of health facility and awareness. Our primary objective is to assess the epidemiology and treatment outcomes of patients with Severe Acute Malnutrition (SAM) admitted to the Nutrition Stabilization Center (NSC) at the Provincial Headquarters Hospital, Gilgit. The study aims to identify key socio-demographic and underlying risk factors influencing the occurrence and progression of SAM in the region.Methods: We examine 226 children's medical records who were admitted with severe acute malnutrition (SAM). Demographic information, anthropometric measurements (weight, Mid Upper Arm Circumference MUAC), health issues, treatment plans, and dietary management techniques were all included in the data., RUTF, ReSoMal, F-75, and F-100 were the therapeutic foods. Treatment results and the length of hospital stay were additional variables. Advanced statistical analyses were carried out using Statistix 8.1. Using age-group stratification, the anthropometric and clinical indicator values at admission and discharge were compared to evaluate nutritional recovery.Results:  Nearly half of the patients were from Gilgit (48.7%), with most referred via OPD (94.2%). Non-oedematous SAM was predominant (94.7%) and new admissions accounted for 95.1%. Common complications included acute gastroenteritis (53.1%), lower respiratory tract infections (22.1%) and sepsis (8.8%). All children received F-75, with variations in additional therapeutic interventions. Mean hospital stay was 8.04 ± 3.30 days, and the cure rate was 91.6%. Significant improvements in weight and MUAC were observed. Children aged 6–10 months showed the highest mean weight gain (0.51 kg), whereas those aged 26–30 months recorded the highest mean MUAC gain (+0.53 cm).Conclusion: SAM management demonstrated positive outcomes, with over 91% recovery and significant anthropometric improvements. Younger children exhibited better weight recovery, while older children showed greater MUAC improvement.